A versatile drug-controlled release polymer brush hybrid non-glutaraldehyde bioprosthetic heart valves with enhanced anti-inflammatory, anticoagulant and anti-calcification properties, and superior mechanical performance. (May 2023) - Yu, Tao; Li, Gaocan; Chen, Xiaotong; Kuang, Dajun; Jiang, Qing; Guo, Yingqiang; Wang, Yunbing
Abstract: Transcatheter heart valve replacement (THVR) is a novel treatment modality for severe heart valves diseases and has become the main method for the treatment of heart valve diseases in recent years. However, the lifespan of the commercial glutaraldehyde cross-linked bioprosthetic heart valves (BHVs) used in THVR can only serve for 10–15 years, and the essential reason for the failure of the valve leaflet material is due to these problems such as calcification, coagulation, and inflammation caused by glutaraldehyde cross-linking. Herein, a kind of novel non-glutaraldehyde cross-linking agent bromo-bicyclic-oxazolidine (OX-Br) has been designed and synthesized with both crosslinking ability and in-situ atom transfer radical polymerization (ATRP) function. Then OX-Br treated porcine pericardium (OX-Br-PP) are stepwise modified with co-polymer brushes of reactive oxygen species (ROS) response anti-inflammatory drug conjugated block and anti-adhesion polyzwitterion polymer block through the in-situ ATRP reaction to obtain the functional BHV material MPQ@OX-PP. Along with the great mechanical properties and anti-enzymatic degradation ability similar to glutaraldehyde-crosslinked porcine pericardium (Glut-PP), good biocompatibility, improved anti-inflammatory effect, robust anti-coagulant ability and superior anti-calcification property have been verified for MPQ@OX-PP by a series of in vitro and in vivo investigations, indicating the excellent application potential as a multifunctional heart valve cross-linking agent for OX-Br. Meanwhile, the strategy of synergistic effect with in situ generations of reactive oxygen species-responsive anti-inflammatory drug blocks and anti-adhesion polymer brushes can effectively meet the requirement of multifaceted performance of bioprosthetic heart valves and provide a valuable reference for other blood contacting materials and functional implantable materials with great comprehensive performance. Graphical abstract: Image 1